2021
DOI: 10.1128/spectrum.01122-21
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Carriage and Molecular Characterization of Carbapenemase-Producing Enterobacterales in the Pediatric Population in Qatar

Abstract: To the best of our knowledge, this is the first study addressing the molecular characteristics of CPE in a pediatric population in Qatar using whole-genome sequencing. Since several countries in the Arabian Peninsula share relatively similar demographic patterns and international links, it is plausible that the molecular characteristics of CPE in children, at least in the middle and eastern parts of the region, are similar to those observed in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Genetic characterization of the 72 isolates indicated the presence of bla NDM-5 (30.8%), bla NDM-1 (19.2%), and bla OXA-181 (19.2%). The authors referred to the apparent sporadic introduction of antibiotic resistance within the healthcare setting in the Arabian Peninsula via asymptomatic carriers, particularly, those who visited or received healthcare in (nearby) countries with endemic antibiotic resistance [ 47 ]. In another study, 149 CRE (89 K. pneumoniae and 38 E. coli ) isolates were found between 2014 and 2017, and the associated genes included bla NDM-1 (30.2%) and bla OXA-48 (19.5%) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Genetic characterization of the 72 isolates indicated the presence of bla NDM-5 (30.8%), bla NDM-1 (19.2%), and bla OXA-181 (19.2%). The authors referred to the apparent sporadic introduction of antibiotic resistance within the healthcare setting in the Arabian Peninsula via asymptomatic carriers, particularly, those who visited or received healthcare in (nearby) countries with endemic antibiotic resistance [ 47 ]. In another study, 149 CRE (89 K. pneumoniae and 38 E. coli ) isolates were found between 2014 and 2017, and the associated genes included bla NDM-1 (30.2%) and bla OXA-48 (19.5%) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our data revealed the presence of diverse STs and lineages in the region, and most were NDM-type and OXA-48-type producers co-haboring CTX-M ESBL genes. Among them, ST231, ST147 and ST11 were the most prevalent clones, which were different from those isolated from screening rectal swabs in local pediatric populations (7). ST147 (CG147) and ST11 (CG258) are international highrisk clones reported mainly from Asia and Europe and have been responsible for nosocomial transmission and various care-centre outbreaks (21,22), while ST231 was considered an endemic clone disseminating OXA-232 in India (23).…”
Section: Discussionmentioning
confidence: 96%
“…In Qatar, substantial proportions of the population are migrant workers from the Indian subcontinent. Perez-Lopez (7) suggested that CRE in pediatric populations in Qatar were mainly introduced sporadically by asymptomatic carriers who visited or received health care in some nearby countries in which they are endemic. Moreover, consistent with other CRE studies on pediatric and adult patients, genes encoding NDMs and OXA-48 types were widely prevalent in Qatar, the Middle East region, and the Indian subcontinent (7, 22, 24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations